COLLETOTRICHUM FALCATUM CAUSING RED ROT IN SUGARCANE: GENOMIC AND PROTEOMIC APPROACHES TO CHARACTERIZE THE PATHOGENIC VARIATION - Malathi, P; Kaverinathan, K; Scindiya, M; Elamathi, E; Ramesh Sundar, A; Viswanathan, R (Journal of Sugarcane Research, 2020)
Red rot caused by Colletotrichum falcatum, is the major constraint in sugarcane production in India and varietal resistance plays an important role in managing the disease. However, breakdown of resistance in sugarcane varieties to new pathogen variants which co-evolve concurrently is a serious concern and warrants a clear understanding on pathogenic variation in response to virulence. Hence, a detailed study has been carried out through genomic and proteomic approaches to characterize representative group of C. falcatum pathotypes and isolates varying phylogenetically based on 5.8S-ITS sequence analysis. At genomic level the isolates were characterized using conserved gene sequences viz., actin, calmodulin and GPDH and molecular markers viz., RAPD and ISSR. Molecular analyses with conserved gene sequences highly implicated the existence of one major group of virulent isolates and a minor group of least virulent isolates which was confirmed by definite nucleotide variation. Further studies with molecular markers viz., RAPD and ISSR also confirmed separate grouping of least virulent isolates and different groups among the virulent isolates. Among the markers, ISSR was more efficient in grouping the isolates based on virulence, since it clearly differentiated the least virulent isolates like conserved sequences and some of its primers were able to differentiate the virulent isolates with specific markers. For proteomic analysis, a protocol has been standardized to develop C. falcatum proteome profiles of phylogenetically differentiated virulent and least virulent isolates and demonstrated unique and differential expression of spots related to pathogen virulence. Some of the unique proteins viz., serine protease, DJ-1/PfpI family protein and glutathione S-transferase identified from C. falcatum were closer to well characterized pathogenicity related genes in Colletotrichum spp and other fungi. Outcome of the study formed a basis for characterizing virulence related genes in C. falcatum.